Sexual Function in Females With Rheumatoid Arthritis: Relationship With Physical and Psychosocial States - Essam ABDA,; Zahra SELIM,; Samia TELEB,; Mahmoud ZAGHIRA,; Mohamed FAWZY,; Sherifa HAMED, (Archives of Rheumatology, 2016)
Objectives: This study aims to assess the frequency rates of sexual problems and associated factors in a cohort of married females with rheumatoid arthritis (RA). Patients and methods: The study included 200 female RA patients (mean age 44.2±9.1 years; range 18 to 55 years) and 100 age matched healthy control females (mean age 42.5±6.3 years; range 18 to 55 years). Mean duration of RA was 5.8±4.1 years. All participants were assessed by Health Assessment Questionnaire Disability Index, Numerical Rating Pain Scale, Sexual Disability Scale, psychiatric interview, Beck Depression Inventory, and Spielberger's State-Trait Anxiety Inventory. Results: Majority of the patients had grade II physical disability (62%), moderate pain (55%), depression (46%), and anxiety (77%). Sexual disability and loss of sexual desire and satisfaction were reported in 4% to 77.8% of patients which varied with age, duration of RA, degree of physical disability, and psychiatric comorbidities. Multiple regression analysis showed that scores of sexual disability and loss of sexual desire and satisfaction were significantly associated with scores of Health Assessment Questionnaire Disability Index (β=0.347; p=0.018; β=0.501; p=0.001) and depression (β=0.304; p=0.043; β=0.550; p=0.001). Conclusion: We may conclude that the frequencies of sexual problems in females with RA are high and closely related to physical disability and psychiatric comorbidities.